(untitled) (Journal of Engineering, 2003)
This research is concerned with performance of different shapes (parallel plate, grid, corrugated) and materials (polystyrene, polypropylene, P.V.C, and steel) of packing for an air -water- cooling tower. A Mechanical forced draught counter current flow cooling tower of 300 mm x 300 mm, cross-sectional area and 1.65m height was constructed and studied theoretically and experimentally Air flow rates of 0.533,1.035, and 1.774 kg/m2.s were used in conjunction with water flow rates of 1.686, 2.218, and 2.66 kg/m2.s, and water temperature of 40,45,50 °C. The tower characteristics (KG a Z/L) and the volumetric mass and heat transfer coefficients (Kça, hoa and ha) are found to be a function of the water and air flow rates simultaneously.The work was extended to include the longitudinal and transverse temperature profiles within the tower for different parameters.By employing packed heights of polystyrene, and polypropylene of 120,90,60, and 30 cm, end effect were studied and the tower characteristics (KG a Z/L) corrected for these effects. Least square method was used to correlate the experimental results for (Ko a Z/L) in terms of air flux G and water flux L